2022
DOI: 10.21203/rs.3.rs-1927427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinico-Epidemiological Survey of Feline Parvovirus Circulating in Three Egyptian Provinces from 2020 to 2021

Abstract: Feline parvovirus infection (FPV) is the most prevalent cause of fatal gastroenteritis in cats. Only a few reports of FPV infection in cats have been found in Egypt. Therefore, the current study was designed to detect FPV diseased cats in 3 Egyptian provinces. FPV diseased cats was detected based on clinical examination, viral antigen detection using a commercially available screening Ag rapid test kit, and molecular detection of VP-2 gene using specific primers. A total of 100 diseased cats were studied, with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The results revealed that the prevalence of FPV in cats was significantly higher in the Duhok and Sumel regions compared to the Zakho regions. This result is comparable to Abdel-Baky et al [18]; Radhy and Zenad, [19] and Al-Bayati, [21] they found that there is a different prevalence of FPV in cats in various regions of the same country. The difference in prevalence may be related to management practices, cat lifestyles, sampling size, and various climatic factors such as temperature, humidity, and rainfall [18,28,45].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results revealed that the prevalence of FPV in cats was significantly higher in the Duhok and Sumel regions compared to the Zakho regions. This result is comparable to Abdel-Baky et al [18]; Radhy and Zenad, [19] and Al-Bayati, [21] they found that there is a different prevalence of FPV in cats in various regions of the same country. The difference in prevalence may be related to management practices, cat lifestyles, sampling size, and various climatic factors such as temperature, humidity, and rainfall [18,28,45].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the overall prevalence of feline panleukopenia virus (FPLV) disease in cats in Duhok province was 70% using the conventional polymerase chain reaction technique (c-PCR). This result is higher than other studies conducted in Iraq and other countries such as: Baghdad-Iraq was 40%, 21.6% and 13.3% using c-PCR technique, indirect enzyme-linked immunosorbent assay (i-ELISA), and immunochromatography assay (ICA) respectively [19,20], in Ahvaz-Iran was 34.3% using ICA [35], in Burdur, Isparta and Izmit-Turkey was 25% using c-PCR technique [28], in Al Ain-United Arab Emirates was 2.18% using ICA [36], in Suhag, Assiut, and Cairo-Egypt was 35% and 43% using ICA and c-PCR, respectively [18], in Gimcheon-South Korea was 36.4% using quantitative real time polymerase chain reaction (q-PCR) technique [17], in Malang-Indonesia was ICA [37], in Jilin-China was 37.06% using multiplex PCR technique [38], in Bangladesh was 8.16% and 18.37% using ICA and c-PCR, respectively [39], in Bavaria-Germany was 65.8% using virus culture [40], and in Ontario/ Toronto-Canada was 11.72% using q-PCR technique [41]. The prevalence of FPV varied across different regions and countries due to different management approaches, environmental factors, efficient diagnostic techniques used in studies, and the presence or lack of additional parameters such as the host's age, physical condition, and immune status [16,18,20,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations